Faktor-faktor yang mempengaruhi PPAP pada bank syariah dan bank konvensional di Indonesia - PUTRI SARIATI; AAN MARLINAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The purpose of this research is to analyze the influence of return on assets, earnings before taxes and provisions, non-performing loan, capital adequacy ratio, bank type, loan to deposit ratio, size of bank, and listed status to loan loss provision (LLP). This research used national bank include Islamic and conventional bank that listed and not listed in Indonesia Stock Exchange during 2011-2013 as the sample. There are 83 bank and only 128 data meet the criteria by using purposive sampling method. The model used in this research is multiple regression analysis. The result shows that return on assets, earnings before taxes and provisions, and size of bank have signficant effect to LLP. Other independent variables such as non-performing loan, capital adequacy ratio, bank type, loan to deposit ratio, and listed status don’t have any effect to LLP practice in the bank..